Akhlak Bagi Pencari Ilmu - Solich, Moch. (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
The admiration presents the devastation of praiji (hirmone) what is it that is supposed to be for a preaccessous and decree of terror (madzmuh) to be cleaned of the contuisation of the virtuous and reconceived, the true existence of the global era of the global and the great age.So the role of the education Three of education centers, especially family's fundamental education, a society of Education, a society of residence and interact with the environment, and the institution of the massive institution of a more positive, Positive Science, expected to function with the maximum of its exact maximum. If these three elements can operate its own ingenious symptoms, then it can be expected to be born generations of budimented and scholars.